PENGEMBANGAN DAN IMPLEMENTASI APLIKASI PERPUSTAKAAN BERBASIS WEB: DEVELOPMENT AND IMPLEMENTATION OF WEB-BASED LIBRARY APPLICATIONS - Ghea Paulina Suri; Nofri Yudi Arifin (Engineering and Technology International Journal, 2020)
The library is a room managed by an educational institution that provides various kinds of book collections. School is a building or institution for learning and teaching facilities and infrastructure as well as a place for students to receive and give lessons. Technological developments are increasingly cutting-edge, as well as developments in library empowerment today. The library provides a wide collection of information books to read, ranging from textbooks, story books, magazines and others. All collections of these books can be read in the library or borrowed for a certain period of time. In general, libraries only have books that are stored on the shelves of the building or library room, but in today's technological developments use the library by archiving collections of books in the form of digital archives or better known as e-books. Currently, within the scope of education, a quality information system is developed to manage books and provides many benefits such as providing information that can be monitored and can help schools related to the IBNU SINA SMP library web application.